Synthesis of GaN by N ion implantation in GaAs (001) - Lin, X.W. (2016)
Both the hexagonal and cubic GaN phases were synthesized in GaAs ~001! by 50 keV N ion implantation at 380 °C and subsequent furnace annealing at 850–950 °C for 10 min–2 h. For a fluence of 1.531017 cm22, transmission electron microscopy revealed that cubic GaN epitaxially crystallizes as precipitates in the GaAs matrix. A cubic-to-hexagonal GaN phase transition was observed for extended thermal anneals. By increasing the N fluence to 331017 cm22, a continuous buried layer of randomly oriented hexagonal-GaN nanocrystals was produced.